Capacitively Coupled Silicon Modulator Fabricated on the Standard Silicon-on-Insulator Platform - Ahmed Shariful Alam; Hao Sun; Joyce K. S. Poon; Jose Azana; J. Stewart Aitchison (IEEE Photonics Journal)
Silicon-on-insulator (SOI) based silicon modulators are essential for modern optical communication links. Almost all these modulators are based on a rib waveguide structure. In this paper, we report our observation of a silicon modulator in a silicon strip waveguide. Such waveguide have a simpler structure, higher optical confinement, lower dispersion and can result in modulators with improved bandwidth compared to a rib waveguide. We demonstrated a novel strip waveguide-based Mach-Zehnder interferometer (MZI) silicon modulator fabricated in the Multi Project Wafer (MPW) run from a commercial foundry. Using a self-heterodyne measurement system we estimated a half-wave-voltage-length product (V $_{π }$ L) of $\sim$ 9.4 V.cm at 20 MHz modulation signal. The electro-optic (EO) measurement of the proposed modulator can generate the first order sidebands up to 68 GHz and almost a flat frequency response was observed.